Herpes virus bovino, estructura, replicación y latencia (1996)
ABSTRACT: The herpesviruses have been considered among the most complex viral families due not only to their size and their strict replication control but also because of their singular capacity for stablishing latency and reactivation with or without clinical signs. the present article reviews some aspect of the molecular structure of HVB-1, it's replicaction and some of the mechanisms implicated in latency and reactivation of viral infection.